Intrinsic functional connectivity alterations in progressive supranuclear palsy: Differential effects in frontal cortex, motor, and midbrain networks. Issue 7 (22nd May 2017) - Rosskopf, Johannes; Gorges, Martin; Müller, Hans‐Peter; Lulé, Dorothée; Uttner, Ingo; Ludolph, Albert C.; Pinkhardt, Elmar; Juengling, Freimut D.; Kassubek, Jan
Abstract: Background: The topography of functional network changes in progressive supranuclear palsy can be mapped by intrinsic functional connectivity MRI. The objective of this study was to study functional connectivity and its clinical and behavioral correlates in dedicated networks comprising the cognition‐related default mode and the motor and midbrain functional networks in patients with PSP. Methods: Whole‐brain‐based "resting‐state" functional MRI and high‐resolution T1‐weighted magnetic resonance imaging data together with neuropsychological and video‐oculographic data from 34 PSP patients (22 with Richardson subtype and 12 with parkinsonian subtype) and 35 matched healthy controls were subjected to network‐based functional connectivity and voxel‐based morphometry analysis. Results: After correction for global patterns of brain atrophy, the group comparison between PSP patients and controls revealed significantly decreased functional connectivity ( P < 0.05, corrected) in the prefrontal cortex, which was significantly correlated with cognitive performance ( P = 0.006). Of note, midbrain network connectivity in PSP patients showed increased connectivity with the thalamus, on the one hand, whereas, on the other hand, lower functional connectivity within the midbrain was significantly correlated with vertical gaze impairment, as quantified by video‐oculography ( P = 0.004). PSP Richardson subtype showed significantly increased functional motor network connectivity with the medial prefrontal gyrus. Conclusions: PSP‐associated neurodegeneration was attributed to both decreased and increased functional connectivity. Decreasing functional connectivity was associated with worse behavioral performance (ie, dementia severity and gaze palsy), whereas the pattern of increased functional connectivity may be a potential adaptive mechanism. © 2017 International Parkinson and Movement Disorder Society